Construction of Fourier Series Expansion of Apostol-Frobenius-Type Tangent and Genocchi Polynomials (European Journal of Pure and Applied Mathematics, 2023)
In this study, the Fourier series expansions of the Apostol-Frobenius type of Tangent and Genocchi polynomials of higher order are derived using the Cauchy residue theorem. Some novel and intriguing results are obtained by applying the Fourier series expansion of these types of polynomials.
Keywords: Cauchy residue theorem; Fourier series; Tangent polynomials; Bernoulli polynomials; Genocchi polynomials